Operation Enhancement by UPFC for long-term planning of Kurdistan Regional Power System - Majeed, Asso Raouf; Rasheed, Ghamgeen Izat; Abdlmajeed, Dalya Dlshad (Sulaimani Journal for Pure and Applied Sciences, 2018)
The Unified Power Flow Controller (UPFC) is an essential device to control power flow along the transmission lines. In this paper, the power system analyses of Kurdistan Region (KR) electric networks are studied with and without UPFC. The numbers of buses for current Kurdistan Region power system are 176 buses, the numbers of loads are 112 connected load and the total numbers of branches are 254 branches. The proposed networks include long-term planning (2025-2026). Power System Simulation for Engineering (PSS/E) software is used in this work from Electrical Ministry of Kurdistan Region. In this term, the studying of power flow analysis is done using Newton-Raphson (NR) method, and it appeared that the voltage at most nodes are below the allowable limits (0.9-1.1) P.U, therefore UPFC placed in the network, which is consider the forceful device in Flexible AC Transmission System (FACTS) members, to improve the voltage profile, control power flow and minimize real and reactive power flow.
Keywords: FACTS; UPFC PSSE; NR; KR